The Australian Case for Protection Reexamined - Samuelson, M. C. (Quarterly Journal of Economics, 1939)
The Australian Case for Protection Reexamined Get access Marion Crawford Samuelson Marion Crawford Samuelson Radcliffe College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 1_Part_1, November 1939, Pages 143–149, https://doi.org/10.1093/qje/54.1_Part_1.143 Published: 01 November 1939